The influence of electromagnetic processes on stability of locomotives traction drive in the slipping mode - Petr KOROPETS (Transport Problems, 2014)
On the model of a locomotive traction drive in a slipping mode, it is demonstrated how the electromagnetic transient processes in the traction motor may be accounted for using the energy balance method for assessing the stability of the system with respect to frictional self-oscillations. The regions of existence of frictional self-oscillations in the parameter space of the drive are built. The proposed method differs from the prior art in that it can be used to analyze the stability of a wide class of dynamical systems with small damping, containing both oscillatory and inertial units.